MENAKAR PETA ALIRAN SYIAH DALAM ALIRAN KEAGAMAAN PADA DUNIA ISLAM - Muhammadong, Muhammadong (Sulesana, 2023)
The aim of this research is to determine the map of Shiite power in the religious understanding that developed in the Islamic world. Shia as a religious sect in the Islamic world plays an important role in theology and politics. Shia doctrine developed as a result of the Islamic revolution in Iran which sought change through a rationalism-based religious doctrine approach. The understanding of fanaticism developed by the Shiites became an encouragement in spreading the teachings of Islam. They idolized Ali Radiyallahu anhu as the successor to the throne because they considered him very close to the Prophet.